Vitellogenin and vitellogenin receptor gene expression profiles in Spodoptera exigua are related to host plant suitability. Issue 4 (5th January 2018) - Zhao, Jing; Sun, Yang; Xiao, Liubin; Tan, Yongan; Jiang, Yiping; Bai, Lixin
Abstract: BACKGROUND: The beet armyworm Spodoptera exigua, a worldwide phytophagous pest, causes considerable economic agricultural losses. Understanding the relationship between its fecundity and the host plant is a basic and important component of early forecasting of beet armyworm outbreaks. However, little is known about the molecular mechanism by which distinct hosts affect S. exigua fecundity. RESULTS: In this study, key life‐history parameters of S. exigua reared on distinct hosts were investigated; the host plants could be ranked as lettuce > shallot > tomato > celery in their order of suitability. Full‐length S. exigua vitellogenin receptor ( SeVgR ) cDNA was cloned, and sex‐, stage‐ and tissue‐specific expression characteristics were assessed. Spodoptera exigua vitellogenin ( SeVg ) and SeVgR expression levels were markedly modulated by host nutrients ( P < 0.05). SeVg and SeVgR expression levels were significantly higher in S. exigua reared on lettuce, the most preferred and most nutritive host, than in those reared on tomato and celery. Interestingly, significant linear regression correlations were found between SeVg and SeVgR expression levels and key S. exigua life‐history parameters, especially life span, pupa weight, and female fecundity ( P < 0.01). CONCLUSION: Host plant type and suitability could affect the expression pattern of SeVg and SeVgR, which influenced S. exigua fecundity. Vg and VgR have the potential to be used as molecular markers of S. exigua fecundity and for forecasting outbreaks of S. exigua on different hosts. © 2017 Society of Chemical Industry Abstract : This is the first time to prove that host‐plant type and suitability could result in unique expression patterns of SEVg and SEVgR, which influence S. exigua fecundity .